Body Mind Therapy Improving Mental Health in Teenager - Putu Intan Daryaswanti; Ni Made Sri Muryani; Ni Made Diah Pusparini Pendet (Babali Nursing Research)
Background: Mental health has become a critical concern among adolescents, particularly affecting their emotional regulation, problem-solving abilities, and interpersonal relationships. Middle school students are especially vulnerable as they navigate identity formation while being susceptible to external influences. Various factors, including peer pressure, media influence, and gender norms, can exacerbate the gap between adolescents' reality and future perceptions. This study aims to determine the effect of Body Mind Therapy on adolescent mental health.